Surfactant-Free Microwave-Assisted Synthesis of Fe-Doped ZnO Nanostars as Photocatalyst for Degradation of Tropaeolin O in Water under Visible Light. (9th July 2015) - Kwong, Tsz-Lung; Yung, Ka-Fu
Abstract : Iron-doped zinc oxide nanostar was synthesized by the microwave-assisted surfactant-free hydrolysis method. The as-synthesized Fe-doped ZnO nanostars catalyst was fully characterized by scanning electron microscope (SEM), transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDX), powder X-ray diffraction (XRD), and diffuse reflectance UV-vis spectroscopy (UV-DRA). The photocatalytic activity of the photocatalyst was investigated for the photocatalytic degradation of Tropaeolin O under visible light irradiation. It is observed that the doping of Fe ions enhances the absorption of the visible light and thus the photocatalytic degradation rate of Tropaeolin O would increase. Despite the Taguchi orthogonal experimental design method, the photocatalytic conversion could be achieved at 99.8% in the Fe-doped ZnO catalyzed photodegradation reaction under the optimal reaction conditions of catalyst loading (30 mg), temperature (60°C), light distance (0 cm), initial pH (pH = 9), and irradiation time (3 h). The Fe-doped ZnO photocatalyst can also be easily recovered and directly reused for eight cycles with over 70% conversion.